Effectiveness of Instruction Program on Adolescent Girls’ Dietary Habits Diagnosed with Iron Deficiency Anemia - Ezaldeen Alkasab, Hadeel; Aziz, Afifa Radha (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): To evaluate the eating habits of adolescent females’ students and determine the effectiveness of an instructional program on those students about iron deficiency anemia according to serum iron level.Methodology: Pre-experimental design, one group (pre-test and post-test) was carried out in this study at secondary schools in Kirkuk City for the period of April 11 to December 27, 2022. A non-probability (purposive) sample of (62) female students has been selected based on specific criteria. The study tool (a questionnaire) has been designed and constructed based on an extensive review of available literature and related studies. Face validity of the instrument is established through a panel of (13) experts in the different fields. These experts have more than 7 years of experience in their specialist and asked to review and evaluate the instrument format for its content, clarity and adequacy. On basis of their comments and suggestions, some modification was made and changes were performed. Then, the questionnaire was considered valid after taking into consideration their suggestions and recommendations. An instructional program of dietary habits has been given for students with iron deficiency anemia. Descriptive and Inferential statistics was employed to analyze the study data.Results: Pre-test results from the study revealed that 54.8% of students had moderate Iron Deficiency Anemia. While the students' iron levels returned to normal in the posttest (53.2%). The majority of students (59.7%) had poor eating habits at the time of the pretest. While a healthy dietary pattern is present among most of the students (66.1%) at the posttest.Conclusion: This study concluded that the nutrition education program proved a long-lasting strategy to build a good nutritional status and improves public awareness of this problem among the females’ adolescents.Recommendations: More work and creative solutions are needed to create and implement programs to prevent and control iron deficiency anemia in our country. A screening program for Iron Deficiency Anemia in adolescent girls and screening for iron deficiency in high-risk groups should be considered.